1958
DOI: 10.1136/bmj.2.5100.830
|View full text |Cite
|
Sign up to set email alerts
|

Breast and Nipple Pain in Early Stages of Lactation

Abstract: At the end of the electrophoresis (hanging-strip technique) the paper was dried and the haemoglobm bands were photographed unstained.Mrs. K. and in Mrs. P. However, in our experience a rise of the haemoglobin A2 level may be indicative of thalassaemia, but a normal haemoglobin A2 level does not exclude this condition. Summary Haemoglobin J was seen in two unrelated women of Gujerati-speaking Lohana stock. In one of them the haemoglobin J trait was present together with thalassaemia minor. There was no evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

1967
1967
2005
2005

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 7 publications
1
7
0
2
Order By: Relevance
“…In 1950, Newton and Newton reported that that more than 80% of breastfeeding women experienced nipple pain in the postpartum period, whereas Gans (1958) reported that 34% of 1,027 mothers reported nipple pain and 16% experienced cracked nipples in the 1st week after birth. Ziemer, Paone, Schupay, and Cole (1990) documented 96% of the 100 women in their sample experienced nipple pain.…”
Section: Incidence and Duration Of Nipple Painmentioning
confidence: 99%
“…In 1950, Newton and Newton reported that that more than 80% of breastfeeding women experienced nipple pain in the postpartum period, whereas Gans (1958) reported that 34% of 1,027 mothers reported nipple pain and 16% experienced cracked nipples in the 1st week after birth. Ziemer, Paone, Schupay, and Cole (1990) documented 96% of the 100 women in their sample experienced nipple pain.…”
Section: Incidence and Duration Of Nipple Painmentioning
confidence: 99%
“…Infant feeding patterns, as recorded by their mothers, showed no significant change over time, either in frequency ( X 2 [3, N = 15] = 0.5400, p = .91) or in duration of feeds ( X 2 [3, N = 15] = 0.8400, p = .8399). However, a repeated measures MANOVA revealed significant intersubject differences.…”
Section: Resultsmentioning
confidence: 99%
“…Nipple pain is a source of discomfort for many women during the establishment of breastfeeding. The incidence of nipple pain, although difficult to determine, ranges from 42% 2 to 87% 3 …”
mentioning
confidence: 99%
“…Such is the stated opinion of Dummer (1949); Gans (1958); Hughes (1948); Hytten (1954Hytten ( , 1958Pfändler (1949); and Wickes and Curwen (1957). The frequency of "genuine physical incapacity to lactate" has been estimated at 6% of all British mothers by Dummer (1949) and not less than 5% by Spence (1938).…”
Section: Categorymentioning
confidence: 95%
“…This proportion varied from one-to two-fifths of all failures in a number of British studies made under circumstances appearing conducive to breast-feeding, such being the prevailing policy of hospitals and pediatricians. While no author considers it possible to classify women in a clear-cut manner according to their ability to produce breast milk, a number of authors express the opinion that unexplained failures may be "genetic" (Gans, 1958;Hytten, 1954Hytten, */, pp. 1451Hytten, -1452; and papers in their bibliographies).…”
Section: Mothersmentioning
confidence: 99%